Development of a quantitative competitive reverse transcriptase polymerase chain reaction for the quantification of growth hormone gene expression in pigs - Maurício Machaim Franco; Juliana Franco Almeida; Guilherme Rocha Lino de Souza; Robson Carlos Antunes; Luiz Ricardo Goulart (Genetics and Molecular Biology, 2003)
After the advent of the genome projects, followed by the discovery of DNA polymorphisms, basic understanding of gene expression is the next focus to explain the association between polymorphisms and the level of gene expression, as well as to demonstrate the interaction among genes. Among the various techniques for the investigation of transcriptional profiling involving patterns of gene expression, quantitative PCR is the simplest analytical laboratory technique. The objective of this work was to analyze two strategies of a competitive PCR technique for the quantification of the pig growth hormone (GH) gene expression. A pair of primers was designed targeting exons 3 and 5, and two competitive PCR strategies were performed, one utilizing a specific amplicon as a competitor, and the other utilizing a low-stringency PCR amplicon as a competitor. The latter strategy proved to be easier and more efficient, offering an accessible tool that can be used in any kind of competitive reaction, facilitating the study of gene expression patterns for both genetics and diagnostics of infectious diseases.